Jane, unlimited - Cashore, Kristin (Kathy Dawson Books, 2017)
Mourning her aunt, Jane, who is obsessed with making umbrellas, is swept away by an acquaintance who encourages Jane to attend a gala on Tu Reviens, an island mansion.